Ephemeral events and their traces in the urban structure: Zagreb’s 1987 Universiade - Petrović Krajnik, Lea; Krajnik, Damir (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Organizing a mega event, even an ephemeral one, can leave many material and non-material traces in a city and a host region and can be a means of bringing to life development visions and urban policy strategy. During preparations for the event itself, numerous interventions are carried out that are directly or indirectly related to the event. Depending on the type and concept of the event itself, the interventions in the city and its region can become part of their permanent heritage, thus improving the long-term quality of life of their inhabitants. The aim of this paper is to show how a large sports event, the 1987 Zagreb Summer Universiade, contributed to the development of the city and the host region, and to the implementation of the urban policy strategy of the time. Although Zagreb has a long history of urban planning, emphasis here is placed on the spatial planning documentation of the second half of the 20th century that preceded the organization of this large sports event. This paper looks at interventions carried out during the preparatory phase of the event that were directly or indirectly related to the temporary event itself as well as at the cultural and social program related to the Universiade. It may be concluded that the 14th Summer Universiade was a significant sports and cultural event that served as an instrument for carrying out numerous projects aimed at constructing new and improving existing sports facilities, accommodation capacities and the urban renewal of the city centre. Since most of the interventions would not have been carried out in such a short period of time were it not for the Universiade, it can be said that the Universiade was a means of realizing urban development policies and renewing Zagreb. The event left a lasting legacy of elements of infrastructure, suprastructure and ecostructure that the inhabitants of the city and the region continue to use for the same purposes.